Implementasi Alat Monitoring Kualitas Udara Berbasis Internet of Things (IoT) di Wilayah Industri Pertambangan Nikel - Asdar Asdar; Ana Mustika; Miranda Miranda; Nurtani Nurtani; Triani Triani; Bardan Bulaka (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze air quality in areas affected by industrial and nickel mining activities using Internet of Things (IoT)-based monitoring tools. The research used a quantitative descriptive method with a field study approach, which was carried out in two locations with different characteristics, namely the Tambea Village Office as an area far from the mining area and the Sangia Nibandera Kolaka Meteorological Station (BMKG Kolaka) which is located near the nickel mining industrial area. The monitoring system is designed using an ESP32 microcontroller integrated with an MQ-135 sensor to detect polluting gases, a DHT11 sensor to measure temperature and humidity, and is equipped with a buzzer and OLED display. Data is sent in real-time through the Blynk app. The measurement results showed that the air quality in Tambea Village was mostly in the